Patient Experience and Handling Complaints of Loyalty: The Role of Trust Interventions - Afidahtin, Aap (Journal of Hospital Management, 2025)
This study is based on initial observation results which show a decrease in the number of patients who do not use social security payment facilities in 2023. The purpose of this study is to empirically reveal the influence of patient experience and complaint handling on patient loyalty with trust as an intervening variable. The type of research is included in the quantitative with causality design. The population used is non-social security outpatients. The sampling technique uses non-probability, with a calculation that multiplies the number of indicators by 5 observations, so that the number of samples is 240 respondents. The data collection technique used a questionnaire, and the analysis method used the three box method and PLS-SEM analysis. The results of the analysis prove that patient experience and complaint handling have an effect on patient loyalty with trust as an intervening variable. Patient experience and complaint handling affect trust, patient experience, complaint handling and trust affect patient loyalty, and trust is the most dominant variable that is able to increase patient loyalty